Applied anatomy & physiology for manual therapists - Archer, Patricia A.; Nelson, Lisa A. (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2013)
Addresses the needs of students in manual therapy education programs. This title emphasizes the information manual therapists need to be familiar with in order to understand the benefits, effects, indications, and contraindications of their specific form of manual therapy.